Impact assessment of improved wheat variety VL Gehun 907 in Uttarakhand using economic surplus approach - Thakur, Amit; Joshi, Khushagra; Kochar, Janvi; Kant, Lakshmi (Journal of Cereal Research, 2024)
Economic benefits of adopting an improved rust-resistant variety, VL Gehun 907, of wheat in the hill districts of Uttarakhand have been examined. At the field level, variety had a 20-25 per cent yield advantage. The variety adoption was assessed through certified seed demand, which varied from 3 per cent to 27 per cent in the hill region and substantially contributed to wheat production. The economic surplus approach was used for assessing the impact of the high-yielding, rust-resistant variety suitable for rainfed and irrigated timely sown conditions of hills. The estimation approaches, Ex-ante and ex-post, were employed for surplus calculations. At the aggregate level, the ex-post method supplemented with information on adoption rate and output growth, accurately estimates benefits. The total benefits accrued from the investment over nine years amounted to 251 crores. These results speak to reorienting agricultural research to consider the challenges of hill farmers and develop as well as disseminate a higher number of improved varieties suitable for hills to enhance farmers’ socio-economic status and overall agriculture development.